An Analysis of Public Expenditure on Education in Pakistan (The Pakistan Development Review, 2003)
Achieving economic growth is an important goal of any country. However, in recent years it has increasingly been realised that economic growth is a necessary but not a sufficient condition for human development. Pakistan provides a good example of a country which has historically enjoyed a respectable GDP growth rate and yet failed to translate this positive development into a satisfactory level of human development. Since its independence in 1947, Pakistan’s development policies have focused primarily on realising high economic growth and only incidentally on the task of providing social necessities. Such a process has given rise to a structure of production and distribution which has been only indirectly responsive to social goals. However, there is now a growing realisation that we could have done much better had we stressed human resource investments relatively more. The Education For All (EFA) movement, started more than a decade ago in 1990, accelerated the process of human resource development in many developing countries. The EFA refers to the global commitment to ensure that all children would complete Primary Education of good quality. A decade after, the Millennium Declaration resolved to ensure, by 2015, that all children would be able to complete a course of primary education.